Faktor-Faktor Yang Memengaruhi Rendahnya Kepemilikan Jamban Sehat Di Wilayah Kerja Puskesmas Balai Karangan Kecamatan Sekayam Kabupaten Sanggau Kalimantan Barat - Adha Sepria Rafelza; Asriwati Asriwati; Indah Anggraini; Nuraini Nuraini; Endang Maryanti (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2024)
Latrines are effective fecal disposal facilities to break the chain of disease transmission. The purpose of the study was to analyze the factors that influence the low ownership of healthy latrines in the Working Area of Puskesmas Balai Karangan, Sekayam. The research design used the Analytical Survey method with a sectional approach. The population in this study were all people in the Balai Karangan Health Center Working Area, namely 1,984 heads of families. The sample in this study was 95 heads of families with an accidental sampling technique with logistic regression. The results of logistic regression showed that there was an influence of knowledge p = 0.016, attitude p = 0.023, income p = 0.002, availability of clean water p = 0.005, support from health workers p = 0.006 and support from village officials p = 0.024. The dominant factor influencing the low ownership of healthy latrines is income p = 0.002 Exp(B) 337.529. This study concludes that there is an influence of knowledge, attitudes, income, availability of clean water, support from health workers, and support from village officials which does not affect culture. The dominant factor, namely income, influences the low ownership of healthy latrines in the Working Area of Puskesmas Balai Karangan. It is recommended that the Balai Karangan Community Health Center through the Village Head utilize PAMSIMAS by providing pipe assistance or construction of clean water facilities and healthy latrines.